Foundations for common approaches to measure global adaptation actions in the agriculture sector: Highlights from an analysis of existing climate adaptation frameworks - Nowak, Andreea C.; Rosenstock, Todd S. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
"Climate adaptation has been on the back seat of the international policy agenda for many years; the Paris Agreement and relating Global Goal on Adaptation (GGA) provide new momentum to frame adaptation as a global responsibility and to call for collective measurement approaches. n Decisions on potential global adaptation targets and measurements need to build on existing collections of frameworks, indicators and metrics that provide valuable learning opportunities, rather than reinventing processes. n Reviewing what national M&E systems already track in terms of adaptation may be a pertinent way to advance discussions on how the GGA can be translated into practice via bottom-up, country-driven approaches."